Deposition and characterization of silver nano-films by a novel solid liquid interface reaction technique (SLIRT) - Godbole, P. D.; Mitra, A.; Pasricha, R.; Mandale, A. B.; Patil, K. R. (Materials Letters, 2005)
Solid-liquid interface reaction technique (SLIRT) is used to deposit silver film on glass substrate. The solid film of silver nitrate is formed by modified spin coating method. This film is subsequently processed by dipping it in a reducing solution so as to initiate a reaction at the interface and ultimately transform it to totally silver film. In situ transformation of silver nitrate to silver is studied with respect to time spectrophotometrically. The characterization of silver film is done by various physicochemical techniques namely XRD, XPS, ED, TEM and UV visible spectroscopy. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Electron microscopy; Nano-Particles; solid-liquid interface reaction; thin film

Copper phthalocyanine films deposited by liquid-liquid interface recrystallization technique (LLIRCT) - Patil, K. R.; Sathaye, S. D.; Hawaldar, Ranjit R.; Sathe, B. R.; Mandale, A. B.; Mitra, A. (Journal of Colloid and Interface Science, 2007)
The simple recrystallization process is innovatively used to obtain the nanoparticles of copper phthalocyanine by a simple method. Liquid-liquid interface recrystallization technique (LLIRCT) has been employed successfully to produce small sized copper phthalocyanine nanoparticles with diameter between 3-5 nm. The TEM-SAED studies revealed the formation of 3-5 nm sized with beta-phase dominated mixture of alpha and beta copper phthalocyanine nanoparticles. The XRD, SEM, and the UV-vis studies were further carried out to confirm the formation of copper phthalocyanine thin films. The cyclic voltametry (CV) studies conclude that redox reaction is totally reversible one electron transfer process. The process is attributed to Cu(II)/Cu(I) redox reaction. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: Copper phthalocyanine; cyclic voltametry; nanoparticulate films

Synthesis and characterization of mesoporous carbon through inexpensive mesoporous silica as template - Karandikar, Prashant R.; Patil, K. R.; Mitra, A.; Kakade, Bhalchandra A.; Chandwadkar, Asha J. (Microporous and Mesoporous Materials, 2007)
Mesoporous silica materials have been synthesized through sol-gel reaction using inexpensive sodium silicate as source of silica and low cost hydroxy carboxylic acid compounds as templates/pore forming agents. The material measured surface area of 1014 m(2)/g, pore diameter of 65 angstrom and pore volume of 1.4 cc/g when parameters like time and temperature of synthesis along with mole ratio of TA/SiO(2) were optimized. Here TA stands for tartaric acid. Carbonization of sucrose inside the pores of above silica material at 900 degrees C followed by removal of silica framework using aqueous ethanoic solution of NaOH gave rise to mesoporous carbon material. The resulting materials were characterized by N(2)-sorption, FTIR spectroscopy, X-ray diffraction, transmission electron microscopy, X-ray photoelectron spectroscopy, thermal analysis and cyclic voltammetry. Three dimensional interconnecting wormhole channel arrangement of mesoporous silica template leads to mesoporous carbon replica with surface area of 1200 m(2)/g. X-ray photoelectron spectroscopic study (XPS) of the mesoporous carbon material shows the concentration of carbon atom in the range of 97-98% with 1-2% oxygen and negligible amount of silica. The electrochemical double layer capacitance behavior of carbon material with the specific capacitance value of 88.0 F/g at the scan rate of 1 mV/s appears to be promising. (C) 2006 Elsevier Inc. All rights reserved.
Keywords: Electrochemical properties; hydroxy carboxylic acid; mesoporous carbon; Mesoporous silica; sodium silicate